Transition from metabolically benign to metabolically unhealthy obesity and 10-year cardiovascular disease incidence: The ATTICA cohort study - Kouvari, Matina; Panagiotakos, Demosthenes B.; Yannakoulia, Mary; Georgousopoulou, Ekavi; Critselis, Elena; Chrysohoou, Christina; Tousoulis, Dimitrios; Pitsavos, Christos (Metabolism, clinical and experimental, 2019)
Metabolically benign obesity remains a scientific field of considerable debate. The aim of the present work was to evaluate whether metabolically healthy obese (MHO) status is a transient condition which propagates 10-year cardiovascular disease (CVD) onset. A prospective longitudinal study was conducted during 2001–2012, the ATTICA study studying 1514 (49.8%) men and 1528 (50.2%) women (aged >18 years old) free of CVD and residing in the greater Athens area, Greece. Follow-up assessment of first combined CVD event (2011−2012) was achieved in n = 2020 participants; of them, 317 (15.7%) incident cases were identified. Obesity was defined as body mass index ≥30 kg/m2 and healthy metabolic status as absence of all NCEP ATP III (2005) metabolic syndrome components (excluding waist circumference). The MHO prevalence was 4.8% (n = 146) with 28.2% of obese participants presenting metabolically healthy status at baseline. Within this group, 52% developed unhealthy metabolic status during the 10-year follow up. MHO vs. metabolically healthy non-obese participants had a higher likelihood of presenting with 10-year CVD events, yet only the subset of them who lost their baseline status reached the level of significance (Hazard Ratio (HR) = 1.43, 95% Confidence Interval (95% CI) 1.02, 2.01). Sensitivity analyses revealed that MHO status was independently associated with elevated CVD risk in women and participants with low adherence to the Mediterranean diet, low grade inflammation, and insulin resistance. MHO status is a transient condition where weight management is demanded to prevent the establishment of unhealthy cardiometabolic features. The existence of obese persons who remain “longitudinally” resilient to metabolic abnormalities is an emerging area of future research. •About 1 out of 2 strictly defined MHO subjects became unhealthy within a decade.•Transition to unhealthy metabolic status independently increases CVD risk of MHO subjects.•Obesity, without metabolic abnormalities, has stronger aggravating effect for women.•Inflammation and insulin resistance may mediate the MHO status effect on CVD onset.•Nutrition may interact with the combined obesity and metabolic status on CVD risk.